Association between obesity and neurocognitive function in survivors of childhood acute lymphoblastic leukemia treated only with chemotherapy. Issue 17 (29th April 2021) - Iijima, Mayuko; Liu, Wei; Panetta, John C.; Hudson, Melissa M.; Pui, Ching‐Hon; Srivastava, Deo Kumar; Krull, Kevin R.; Inaba, Hiroto
Abstract : Background: Neurocognitive impairment and obesity are common adverse sequelae in survivors of childhood acute lymphoblastic leukemia (ALL); however, the association has not been investigated. Methods: Neurocognitive function was evaluated once in survivors of ALL who were at least 8 years old and 5 years from their diagnosis. In a cross‐sectional analysis, the associations with the body mass index (BMI) category and Z score were examined. A longitudinal analysis used the overweight/obesity area under the curve (AUC), which was determined via the trapezoidal rule by a sum of the integrals defined by the BMI Z score at each time point and the time intervals of the BMI measurement. Results: For 210 survivors, the median BMI Z score at diagnosis was 0.17, which increased to 0.54 at the end of induction and to 0.74 at the neurocognitive assessment. In the cross‐sectional analysis, overweight/obese survivors scored significantly lower than others on the measures of executive function (cognitive flexibility, planning, verbal fluency, working memory, and spatial construction; all P < .05), attention (attention span and risk taking; all P < .05), and processing speed (visual motor coordination, visual speed, and motor speed; all P < .05). In the longitudinal analysis, when the treatment period was subdivided into 4 time periods (induction, consolidation, early maintenance, and late maintenance), a greater overweight/obesity AUC during induction therapy was associated with worse cognitive flexibility ( P = .01) and slower motor speed ( P = .02), which persisted throughout the treatment. Conclusions: Overweight/obesity was significantly associated with neurocognitive impairment during long‐term follow‐up, and this association started early in treatment for ALL. Novel early interventions to provide cognitive training and prevent weight gain are required for patients at risk. Abstract : In a cohort of 210 children with acute lymphoblastic leukemia (ALL) at a median follow‐up of 7.5 years from diagnosis, overweight/obese survivors score significantly worse than others on measures of neurocognitive performance. This association with overweight/obesity status is already seen during induction therapy, and this suggests that early multidisciplinary interventions should be implemented to prevent obesity and to alleviate adverse neurocognitive sequelae in survivors of ALL.